Research on path curvature smoothing method based on energy function for intelligent vehicles - Qiang SHI; Ming YANG (智能科学与技术学报)
Intelligent vehicles are of great significance in social efficacy such as prevention of traffic accidents,ease traffic congestion and reducing emissions.Path tracking is an important part of intelligent vehicles function,whose controlled object is a complex vehicle-road coupling system.Path curvature smoothness affects path tracking performance.A curvature smoothing method based on energy function was proposed to optimize the smoothness of path curvature.Firstly,an energy function was constructed to characterize the path curvature smoothness.Secondly,aniteration rule was designed to reduce the energy function based on discrete path description.Finally,the constraint of road boundary was considered when the road boundary was known.The experimental results of the real vehicle platform show that the energy function smoothing method can further improve the ride comfort and control accuracy of path tracking on the premise of ensuring the path feasible.The quality of intelligent vehicles is improved.